2021
DOI: 10.1002/joc.7098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of precipitation simulations in CMIP6 models over Uganda

Abstract: This study employed 15 CMIP6 GCMs and evaluated their ability to simulate rainfall over Uganda during 1981-2019. The models and the ensemble mean were assessed based on the ability to reproduce the annual climatologyseasonal rainfall distribution, trend, and statistical metrics, including mean bias error, root mean square error, and pattern correlation coefficient.The Taylor diagram and Taylor skill score (TSS) were used in ranking the models. The models performance varies greatly from one season to the other.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 88 publications
2
44
0
Order By: Relevance
“…The two main projections utilized are drawn from Tier 1 ScenarioMIP: SSP2-4.5 and SSP5-8.5. Following the recommendations of previous studies (e.g., [57,[81][82][83][84][85]), this employs MME of CMIP6 for projection of extreme events over the study area. Many studies have remarked on the robustness of MME as compared to individual models due to cancellation of intermodel biases [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two main projections utilized are drawn from Tier 1 ScenarioMIP: SSP2-4.5 and SSP5-8.5. Following the recommendations of previous studies (e.g., [57,[81][82][83][84][85]), this employs MME of CMIP6 for projection of extreme events over the study area. Many studies have remarked on the robustness of MME as compared to individual models due to cancellation of intermodel biases [59].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of complex topography has considerable influence on the variation of extreme events and impacted regions [66,83]. For instance, the presence of large inland water bodies-i.e., Lake Victoria, which is the largest freshwater lake in Africa and second in the world, covering about 68,000 km 2 and bordering three countries, Uganda (45%), Tanzania (49%), and Kenya (6%)-have a significant influence on the incidences of extreme events [84]. Additionally, high elevation areas (i.e., Mt.…”
Section: Discussionmentioning
confidence: 99%
“…While we used biascorrected CMIP6 simulations to examine the future changes in precipitation and PET over WMZs across Uganda, the results should be interpreted with caution due to few limitations. Existing studies have pointed out the simulated precipitation over Uganda and the Greater Horn of Africa depends on the boundary layers, the model horizontal resolution, and the parameterization schemes [51][52][53][54]. In fact, in a recent study over East Africa [55] established that the biases in GCMs are not fully corrected to resemble observed patterns, despite the implementation of various robust statistical methods such as quantile approach.…”
Section: Discussionmentioning
confidence: 99%
“…The student t test is used to calculate significant values at the 99% confidence interval. As noted by other CMIP6 model simulation evaluation studies (e.g., Akinsanola et al, 2021;Ngoma et al, 2021), CMIP6 model simulations generally show biases in representing regional precipitation patterns. For the current study domain, biases shown could be resulting from, among other factors, local climate and mesoscale convective systems (Ridder et al, 2021) and the general complexity of East Africa's large-scale controlled climate (Li et al, 2016;Nicholson, 2017).…”
Section: Methodsmentioning
confidence: 50%